Uji Formulasi Pupuk Hayati Tepung Berbahan Aktif Bacillus sp. pada Bibit Karet (Hevea brasiliensis) Stum Mini - Khoiri, M. Amrul; Puspita, Fifi; Rumapea, Denny Swardi (Jurnal Agro Teknologi Tropika, 2015)
Rubber plants (Hevea brasiliensis) is a important crop plantations in Indonesia and because contributor offoreign exchange after oil palm. The study aimed to examine the effect of bio-fertilizer formulations powder containactive Bacillus sp. and get the best formulations on the growth of rubber seedlings (Hevea brasiliensis) mini stumb. Theresearch was conducted at the Laboratory of Plant Pathology Faculty of Agriculture and the technical implementationunit of agriculture faculty of Riau University, in December 2014 until May 2015. The methods of research is experimentallywith using completely randomized design (CRD) with 5 treatments and 4 replications. The data were analyzed statisticallywith using analysis of variance and followed by Duncanâs New Multiple Range Test at level Ã¡ = 5%. The parametersmeasured were increase of seedling height increment, stem circumference, in the number of leaves, the ratio of crownroots and dry weight. The results of the research showing aplication formulations of Bacillus sp. were tested hassignificant effect on seedling height increment and the number of leaves but not real effect on stem circumference, theratio of crown roots and dry weight. Formulations Bacillus sp. with material peat is the best formulation to influenceseedling height increment and the number of leaves seed rubber mini stumb.